2015
DOI: 10.3171/2015.1.focus14745
|View full text |Cite
|
Sign up to set email alerts
|

Molecular features assisting in diagnosis, surgery, and treatment decision making in low-grade gliomas

Abstract: The preferred management of suspected low-grade gliomas (LGGs) has been disputed, and the implications of molecular changes for medical and surgical management of LGGs are important to consider. Current strategies that make use of molecular markers and imaging techniques and therapeutic considerations offer additional options for management of LGGs. Mutations in the isocitrate dehydrogenase 1 and 2 (IDH1 and IDH2) genes suggest a role for this abnor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0
7

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 49 publications
(33 citation statements)
references
References 40 publications
0
26
0
7
Order By: Relevance
“…The preoperative knowledge of the IDH1 status is of major interest for further patient management/surgical strategy since it was shown in a recent study that the IDH1 mutational status has a crucial impact on the surgical benefit: While patients with IDH1 wild-type malignant gliomas do not profit from further removal of the non-enhancing tumour in addition to the enhancing tumour, this surgical strategy results in a significantly prolonged overall survival in patients with IDH1 mutant tumours [12, 13]. Interestingly, we observed a significantly higher mean SWI-LIV in IDH1-R132H negative compared to IDH1-R132H positive gliomas.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The preoperative knowledge of the IDH1 status is of major interest for further patient management/surgical strategy since it was shown in a recent study that the IDH1 mutational status has a crucial impact on the surgical benefit: While patients with IDH1 wild-type malignant gliomas do not profit from further removal of the non-enhancing tumour in addition to the enhancing tumour, this surgical strategy results in a significantly prolonged overall survival in patients with IDH1 mutant tumours [12, 13]. Interestingly, we observed a significantly higher mean SWI-LIV in IDH1-R132H negative compared to IDH1-R132H positive gliomas.…”
Section: Discussionmentioning
confidence: 99%
“…More and more, molecular markers such as the IDH1 mutational status are increasingly incorporated in clinical decision making in addition to the tumour grade. Furthermore, it has been recently demonstrated that IDH1 mutant gliomas particularly profit from aggressive tumour resections [12, 13]. Similarly to different microvascular patterns in gliomas of various grades of malignancy, neo-angiogenesis, and thus formation of pathological microvessels was found to be associated with IDH1/2 mutational status with increased neo-angiogenesis in IDH1/2 wild-type gliomas and inhibition of neo-angiogenesis in IDH1/2 mutant tumours [14].…”
Section: Introductionmentioning
confidence: 99%
“…The generally small study size is dangerous as inclusion of patients with a more favorable tumor biology in some studies could result in better survival and erroneous conclusions about treatment efficacy when comparing different subgroups. The impact of certain biological features has only been realized in recent years (96)(97)(98). In addition, some studies included patients with histological grade change, e.g.…”
Section: Resultsmentioning
confidence: 99%
“…Studies have shown that the standard of care for 1p/19q co-deleted oligodendroglial tumors should be the combination of CHT and radiotherapy (RT). In OA, a favourable prognosis was associated to young age, grade II and extent of resection [26].…”
Section: Treatment and Prognosismentioning
confidence: 98%